The Demigod Files - Riordan,Rick (Newyork Hyperion Books, 2009)
The Demigod Files is a companion book to the Percy Jackson and the Olympians series. It was released on February 10, 2009. It contains three short stories that are all in Percy Jackson's perspective. The stories are Percy Jackson and the Stolen Chariot, Percy Jackson and the Bronze Dragon, and Percy Jackson and the Sword of Hades.
The Demigod Files is a series of Percy Jackson and the Olympians.
Keywords: Mythology, Greek-Fiction -- Monsters-Fiction